Total Mechanical Intestinal Obstruction due to Intrarectal Foreign Body: A Case Report and Comprehensive Literature Review on Surgical Approaches and Pathophysiological Analysis of the Suction Effect - Bimo Nugroho Sakti; Saiful Islam; Edwin Christian Tjiomas; Wibowo Suryo Pambudi (The International Journal of Medical Science and Health Research, 2026)
Introduction Retained rectal foreign body (RFB) represents one of the most challenging and unique clinical presentations in surgical emergency departments worldwide. (1) This condition is often shrouded by social stigma, embarrassment, and cultural barriers, leading patients to delay seeking medical help until life-threatening complications, such as total mechanical intestinal obstruction or colonic perforation, develop. (1) This case report presents the surgical management of a young male patient with acute intestinal obstruction due to a plastic bottle lodged in the rectosigmoid area. Case Illustration A 24-year-old male presented to the emergency department complaining of a plastic bottle inserted into the anus one hour before hospital admission. The patient reported an inability to remove the object independently, accompanied by nausea, abdominal bloating, and loss of ability to pass flatus. Physical examination revealed increased bowel sounds and suprapubic tenderness. Laboratory examination revealed leukocytosis (13,440 / µL), indicating an initial inflammatory response to bowel distension. (6) Plain abdominal radiography (BNO) confirmed the presence of a cylindrical foreign body in the rectosigmoid area. The patient underwent emergency exploratory laparotomy for foreign body evacuation via the intra-abdominal "milking" technique after transanal extraction attempts failed. Discussion RFB management requires a "step-up" algorithm approach, ranging from bedside extraction to open surgical intervention. (11) The failure of manual extraction in this case was due to the large diameter of the bottle and the "suction effect," or vacuum effect, created against the rectosigmoid mucosa. (12) The use of broad-spectrum prophylactic antibiotics such as intravenous Ceftriaxone 1 g proved effective in preventing surgical site infection (SSI) in emergency colorectal surgery procedures. (15) Conclusion Early diagnosis through radiological imaging and careful clinical evaluation is crucial for determining a safe evacuation strategy. (18) Although transanal techniques are the first line, exploratory laparotomy remains the definitive choice to prevent iatrogenic injury in cases of foreign bodies tightly lodged in the proximal rectum. (9) Keywords Rectal Foreign Body, Mechanical Intestinal Obstruction, Exploratory Laparotomy, Rectosigmoid, Colon Pathophysiology.